(untitled) (CIPEEX, 2024)
INTRODUCTION: HEALTH-RELATED JUDICIALIZATION IN BRAZIL IS A COMPLEX PHENOMENON WITH PROFOUND IMPLICATIONS FOR THE COUNTRY’S HEALTHCARE SYSTEM. ADDRESSING SOCIODEMOGRAPHIC AND LEGAL ASPECTS OF JUDICIAL DEMANDS AND THE INFLUENCE OF FACTORS SUCH AS THE VALUATION OF MEDICATIONS AS HEALTHCARE NECESSITIES, THE PURSUIT OF EQUITY IN THE HEALTHCARE SYSTEM, AND COMPLIANCE WITH PUBLIC POLICIES. OBJECTIVE: TO ANALYZE THE INCREASING JUDICIALIZATION OF ACCESS TO MEDICATIONS IN THE BRAZILIAN CONTEXT. METHOD: WE CONDUCTED AN INTEGRATIVE REVIEW BY SEARCHING THE PUBLIC MEDICINE DATABASE AND THE VIRTUAL HEALTH LIBRARY USING VARIOUS COMBINATIONS OF HEALTH SCIENCE DESCRIPTORS, SUCH AS "JUDICIALIZATION OF HEALTHCARE," "PUBLIC HEALTH," AND "PHARMACEUTICAL PREPARATIONS." INCLUSION CRITERIA COVERED ORIGINAL ARTICLES PUBLISHED IN THE LAST FIVE YEARS WRITTEN IN ENGLISH AND PORTUGUESE&NBSP;WHILE TEXTS UNRELATED TO THE RESEARCH TOPIC WERE EXCLUDED. RESULTS: ANALYZING LEGAL PROCEEDINGS RELATED TO MEDICATION REQUESTS REVEALED A RECURRING PATTERN: A PREDOMINANCE OF FEMALE AUTHORS WITH AN AVERAGE AGE OF 48.3 YEARS, THE MAJORITY RESIDING IN RURAL AREAS. PUBLIC LEGAL ASSISTANCE PLAYED A CRUCIAL ROLE, REPRESENTING 52.8% OF THE CASES. MANY REQUESTED MEDICATIONS WERE ABSENT FROM THE NATIONAL LIST OF ESSENTIAL MEDICINES (RENAME), INDICATING A GAP IN THE COVERAGE OF THE UNIFIED HEALTH SYSTEM (SUS). HOWEVER, IN 68% OF CASES, ACCESS TO THE MEDICATIONS WAS GRANTED, WITH AUTHORS THEMSELVES RESPONSIBLE FOR THE PURCHASE IN 56.1% OF THOSE CASES, OFTEN THROUGH THE BLOCKING OF PUBLIC FUNDS. THE ANALYSIS ALSO HIGHLIGHTED THE PREVALENCE OF CHRONIC DISEASES IN LEGAL DEMANDS AND REQUESTS FOR MEDICATIONS NOT AVAILABLE THROUGH SUS. ANOTHER ANALYSIS IDENTIFIED AN INCREASED DEMAND FOR LEGAL ACTIONS STARTING IN 2017, WITH A REPETITION OF THE PROFILE OF CLAIMANTS. PUBLIC LEGAL ASSISTANCE PLAYED A PIVOTAL ROLE, REPRESENTING 76.8% OF THE CASES. SOME DEMANDS WERE RELATED TO NEGLECTED TROPICAL DISEASES, ALBEIT IN FEWER NUMBERS. A THIRD STUDY FOCUSED ON THE MUNICIPAL DISTRIBUTION OF LEGAL ACTIONS, FINDING STATISTICAL ASSOCIATIONS BETWEEN THE NUMBER OF BENEFICIARIES AND INDICATORS SUCH AS THE MUNICIPAL HUMAN DEVELOPMENT INDEX (IDHM), THE HEALTH VULNERABILITY INDEX (IVS), AND THE POPULATION SIZE OF MUNICIPALITIES, INDICATING SIGNIFICANT VARIATIONS IN THE DISTRIBUTION OF LEGAL ACTIONS BASED ON SOCIOECONOMIC FACTORS. FINALLY, AN ADDITIONAL ANALYSIS REVEALED THAT 60.7% OF REQUESTED MEDICATIONS WERE NOT PART OF THE RENAME, AND IN 75% OF CASES, THERAPEUTIC ALTERNATIVES WERE AVAILABLE THROUGH SUS. PRESCRIBERS FROM PHILANTHROPIC AND PRIVATE SERVICES OFTEN REQUESTED MEDICATIONS NOT COVERED BY PHARMACEUTICAL ASSISTANCE POLICIES. EVEN NATIONALLY LISTED MEDICATIONS WERE FREQUENTLY REQUESTED FOR NON-STANDARD INDICATIONS. CONCLUSION: THESE RESULTS UNDERSCORE THE COMPLEXITY OF HEALTHCARE JUDICIALIZATION IN BRAZIL AND ITS MULTIFACETED NATURE. THE JUDICIAL ROUTE HAS BECOME A MEANS TO ACCESS MEDICATIONS NOT INCORPORATED INTO SUS, BUT ALSO RESULTS IN THE BLOCKING OF PUBLIC FUNDS, HINDERING THE EXECUTION OF PHARMACEUTICAL ASSISTANCE POLICIES. THE ANALYSES ALSO EMPHASIZE THE IMPORTANCE OF EFFECTIVE FOLLOW-UP AFTER JUDICIAL DECISIONS TO ENSURE THE APPROPRIATE USE OF MEDICATIONS AND ASSESS THE HEALTHCARE OUTCOMES FOR PATIENTS, GIVEN THE SIGNIFICANT INFLUENCE OF LEGAL ACTIONS ON THE MANAGEMENT OF PUBLIC RESOURCES AND COMPLIANCE WITH PUBLIC HEALTH REGULATIONS.